NCOG-33. HEMATOLOGIC PREDICTORS OF OUTCOMES IN GLIOBLASTOMA TREATED WITH SURGERY AND CHEMORADIATION. (9th November 2020) - Damico, Nicholas; Elder, Theresa; Kharouta, Michael; Sloan, Anthony; Kerstetter-Fogle, Amber; Harris, Peggy; Kumar, Aryavarta; Mansur, David; Machtay, Mitchell; Bhatt, Aashish; Buerki, Robin; Sloan, Andrew E; et al.
Abstract: BACKGROUND: There are conflicting reports regarding the prognostic value of platelet and other blood counts in glioblastoma. However, few series have looked at all hematologic parameters simultaneously. METHODS: We performed a retrospective chart review of patients diagnosed with supratentorial glioblastoma from 2014-2019 who started conventional chemoradiation following initial surgical biopsy and/or resection. Hematologic parameters were collected at baseline, in the preoperative and postoperative periods and at the initiation and completion of chemoradiation. This included platelet counts, hemoglobin levels, white blood cell counts (WBC), neutrophil and lymphocyte counts with neutrophil:lymphocyte (NLR) and platelet:lymphocyte ratios (PLR) calculated at each time point. Cox regression was performed to assess the association between each hematologic parameter and both overall survival (OS) and progression free survival (PFS). A multivariate Cox proportional hazards model adjusted for all hematologic parameters, age, sex, race and KPS was generated for each time point. All hematologic parameters were modeled as continuous variables. RESULTS: A total of 58 patients met inclusion criteria. 18 were female and 40 male. The median age was 59.5 (range 43-82). Median follow up for all patients was 15.3 months. A total of 52 patients completed radiation therapy and 18 completed 6 cycles of adjuvant chemotherapy. Hemoglobin and neutrophil counts at the conclusion of chemoradiation were associated with OS and PFS on univariate and multivariate analyses. The HR for OS were 0.74 (95% CI 0.5807-0.9313) and 1.28 (1.143-1.441) respectively. The HR for PFS were 0.70 (0.5531-0.8881) and 1.16 (1.05-1.271) respectively. Postoperative lymphocyte and platelet counts at initiation of chemoradiation were both associated with OS with unadjusted HR of 3.2 (1.037-9.960) and HR of 0.99 (0.9898-0.9999) respectively, which remained significant on multivariate analysis. However, neither were associated with PFS. CONCLUSION: Several hematologic parameters are associated with glioblastoma outcomes in these initial analyses. Further analyses with additional patients are ongoing.